Minimizing Surface Roughness and Radius Error in Laser Cutting of EN10346 Steel Plate - Kangal, A. Mustafa; Uysal, Alper; Dzhemilov, Eshreb; Dzhemalyadinov, Ruslan (SPRINGER-VERLAG SINGAPORE PTE LTD, 2021)
In this study, the effects of cutting parameters on radius error and surface roughness during laser cutting of EN10346 (DX51D + Z) hot-dip rolled galvanized steel plate were discussed. The process parameters were chosen based on the literature and technical catalog of the laser machine tool. The experiments were planned according to the Taguchi L-9 design of experiments to reduce the number of experiments. After laser cutting operations, the surface roughness values were measured by the Mituyoto Surftest SJ-210 surface roughness measurement device, and the edge radius values were measured by Mshot MD30 microscope. The optimum cutting parameters for minimum surface roughness were calculated as laser power of 4 pi W, feed rate of 5000 m/min, frequency of 4 kHz, and focus of -0.5. This combination was confirmed with the minimum surface roughness of 2.241 mu m. The optimum cutting parameters for minimum radius error were calculated as laser power of 2 kW, feed rate of 4000 mm/min, frequency of 5 kHz, and focus of -0.8. This result was also confirmed with the minimum radius error of 0.08%.
Keywords: Laser cutting; EN10346 steel plate; Radius error; Surface roughness; SENSOR; Engineering